American Protestants and U.S. Foreign Policy toward the Soviet Union during the Eisenhower Administration: Billy Graham, Reinhold Niebuhr, and G. Bromley Oxnam - Davis, Aaron K. (Kansas State University, 2017)
This dissertation considers American Protestant perceptions of U.S. foreign policy directed toward Soviet Union during the Dwight D. Eisenhower presidency (1953-1961). The question of what a culture dominated by Protestant denominations thought of its global adversary has not yet been sufficiently explored by scholars of either American religious history or diplomatic history. Most scholars who deal with the intersection of religion and foreign policy during the Eisenhower Administration tend to accentuate the close relationship that existed between government policy and general religious attitudes. That is to say, a general, widespread Protestant support of foreign policy objectives stands as the prevailing interpretation. Most historians conclude that America’s Protestant church leaders—preachers, pastors, and bishops—either actively supported government foreign policy objectives or sought to insert their own stances into existing policy. More recently, historians have published monographs that further explore Protestant Christianity with regard to foreign policy in the 1950s. By acknowledging the different strands of Protestant Christianity, scholars have raised significant questions that have heretofore gone unanswered. The primary question is the one that this dissertation seeks to answer—how widespread was American Protestant denunciation of communism and, simultaneously, how broad was American Protestant support for foreign policy objectives? Billy Graham, Reinhold Niebuhr, and Garfield Bromley Oxnam represent the three most prominent representatives of Protestant Christianity’s three major strands. These three acknowledged opinion makers that serve as the focus of this dissertation were not uniform in their perspectives of U.S. foreign policy, yet they all denounced communism and—to a degree—supported America’s efforts to combat the Soviet Union’s sphere of influence throughout the course of the Eisenhower Administration (1953-1961). This conclusion helps explain the tremendous perseverance of containment as a strategy by attributing its success, in part, to the large, Protestant body of supporters that continued to sustain and encourage Washington’s policies directed toward the Soviet Union.
Keywords: Religion; Foreign policy; Cold War; American Protestants